Le donne nella costruzione dell’Europa di domani - Melchionni, Maria Grazia (Rivista di studi politici internazionali, 2009)
ABSTRACT - The role of women in the building of Europe is retraced by the Author to the thought of Simone Weil, Maria Zambrano, Hannah Arendt, the philosophers who, having experienced first hand the crisis of civilisation and the historic and political catastrophe of Europe in the twentieth century, have foreseen the death of the old European system of States and, particularly the last one, looked forward to the European uniting. Their great contributions to the European discourse, however, developed far from the centres of power and did not have direct effects on the transformation of the inter-European relations. Therefore the Author recalls some female figures – such as Louise Weiss, Simone Veil, Ursula Hirschmann –, who already have historical status for having been involved in European political action, and shows how women’s agenda for Europe was focused on concrete problems. The Author underlines the necessity for women’s participation in perfecting the process of integration and making Europe more democratic, economically vital, socially stable and culturally complete, but also stresses the fact that the contribution of women to the Europe of tomorrow will depend on the development of the process of female emancipation in all European countries. RÉSUMÉ - Le rôle des femmes dans l’histoire de l’intégration européenne est pris en considération par l’Auteur à partir de la contribution au discours européen donnée par trois philosophes – Simone Weil, Maria Zambrano et Hannah Arendt –, qui, ayant expérimenté personnellement la crise de la civilisation et la catastrophe politique et historique de l’Europe au vingtième siècle, ont envisage la fin du vieux système européen des États et, surtout la dernière d’entre elles, ont réfléchi sur l’unité européenne. Cependant, étant loin des centres du pouvoir, ces femmes remarquables par leur esprit n’ont pas influé sur la transformation des relations entre les États européens. L’Auteur examine alors les effets sur la construction européenne de l’action politique de trois personnalités de grande envergure – Louise Weiss, Simone Veil, Ursula Hirschmann –, et montre que leur agenda pour l’Europe était centrée sur des problèmes concrets. Tout en soulignant la nécessité que les femmes participent à l’accomplissement du processus d’intégration pour que l’Europe soit plus démocratique, économiquement vitale, socialement stable et riche au point de vue culturel, il fait remarquer que le rôle des femmes dans l’Europe de demain dépendra du développement de l’émancipation de la femme dans les pays membres.